Pembuatan Arsitektur Data Di Perusahaan X - Cornelius Juvian Limanto; Lily Puspa Dewi; Adi Wibowo (Jurnal Infra, 2016)
Company X is a company engaged in the field of automotive dealers in Surabaya. Company X currently has a target of business conducted in its business processes. Target businesses works for this time is Sales process. For Sales process, the company X is supported by a program created by the programmer freelancer. Currently the company X to develop into larger business goals. Target business they want to develop is service and spare parts. Company X has a constraint in the use of programs that are already available today. The less dynamic programs to do the addition and got a constraint if there is a fault of the program, because the company had to wait for a team of freelancers who make programs for doing improvements on that program. Company X requires the existence of a new program that could support the business targets which can also be diintergrasikan with the new business targets. With analysis and design-making enterprise architecture Enterprise Architecture Planning method is expected to help the company in its decision making in the field of IT.